Cervical ICA pseudo-occlusion on single phase CTA in patients with acute terminal ICA occlusion: what is the mechanism and can delayed CTA aid diagnosis?. (6th February 2018) - Wareham, James; Crossley, Robert; Barr, Sarah; Mortimer, Alex
Abstract : Background: Single-phase CT angiography (CTA) forms the basis of hyperacute stroke imaging but many patients with terminal internal carotid artery (ICA) occlusion exhibit a pseudo-occlusion of the cervical ICA whereby a column of unopacified blood mimics a tandem cervical ICA lesion. We aimed to investigate the utility of a delayed phase acquisition to aid identification of a pseudo-occlusion and investigated the mechanism for this imaging artefact. Methods: Thirteen patients with a pseudo-occlusion were compared with 13 patients without. CT, CTA, and digital subtraction angiographic images were reviewed by two interventional neuroradiologists for extension of thrombus into the ophthalmic segment, filling of the posterior communicating artery and ophthalmic artery, and for extension of contrast beyond the cervical segment and outline of the proximal clot surface by contrast on delayed imaging performed at 40 or 80 s. Results: Those with a pseudo-occlusion demonstrated more frequent thrombus extension into the ophthalmic segment (100% vs 23%, P=0.0001), less frequent filling of the posterior communicating artery (15% vs 85%, P=0.0012), and less frequent filling of the ophthalmic artery (15% vs 92%, P=0.0002) compared with those without a pseudo-occlusion. Delayed CTA imaging showed contrast beyond the cervical segment and meeting the proximal clot face in 2/11 patients. Each of these two patients showed patency of the posterior communicating artery origin. Conclusion: Thrombus extension into the ophthalmic segment and patency of the posterior communicating artery and ophthalmic artery seem to govern whether a patient with a terminal ICA occlusion exhibits a pseudo-occlusion. Delayed imaging was of limited value in identification of a pseudo-occlusion.